2015
DOI: 10.3892/etm.2015.2469
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of black-blood high-resolution magnetic resonance imaging for intracranial atherosclerotic plaques

Abstract: Abstract. The present study evaluated the value of black-blood high-resolution magnetic resonance imaging (HRMRI) for the visualization of intracranial atherosclerosis (ICAS) plaques. A total of 110 patients with cerebral artery or vertebrobasilar stenosis, vessel occlusion or a significantly weakened signal in black-blood magnetic resonance angiography (MRA; three-dimensional time-of-flight) were examined. Black-blood MRA was used to observe whether plaques were present in the abnormal vascular walls. Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…HR-MRI has an outstanding effect in differentiating atherosclerotic plaque, vasculitis, reversible cerebral vasoconstriction syndrome, and arterial dissection ( 3 8 ). Compared with other traditional lumen imaging techniques, HR-MRI has been found to be more accurate in determining the extent of atherosclerotic lesions ( 23 , 24 ). Klein et al ( 25 ) studied 41 patients with pontine infarction and found that HR-MRI was superior to TOF MRA in detecting basilar atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…HR-MRI has an outstanding effect in differentiating atherosclerotic plaque, vasculitis, reversible cerebral vasoconstriction syndrome, and arterial dissection ( 3 8 ). Compared with other traditional lumen imaging techniques, HR-MRI has been found to be more accurate in determining the extent of atherosclerotic lesions ( 23 , 24 ). Klein et al ( 25 ) studied 41 patients with pontine infarction and found that HR-MRI was superior to TOF MRA in detecting basilar atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] By examining 94 cases of abnormal plaque occurrence among 110 patients indicated that the incidence of IS in patients with unstable plaque was significantly higher than patients with stable plaque occurrence. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional (3D) black-blood (BB) contrast-enhanced magnetic resonance imaging (MRI) suppresses the signal of flowing blood and enhances static tissue from the vessel wall [ 6 , 7 ]. Therefore, since 3D BB contrast-enhanced MRI can distinguish the arterial wall from the lumen, intravascular lesions such as atherosclerosis and thromboembolic occlusions can be identified better than other modalities used in neurovascular imaging [ 8 , 9 ]. Since vessel wall lesions are the major cause of cerebral infarction, 3D BB contrast-enhanced MRI may overcome the diagnostic delay of DWI and be helpful in the early detection of stroke [ 9 ].…”
Section: Introductionmentioning
confidence: 99%